2019
DOI: 10.1016/j.cjtee.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Is CT scan a predictor of instability in recurrent dislocation shoulder?

Abstract: Purpose Glenoid bone defect and the defect on the posterior-superior surface of the humerus “Hill-Sachs lesion” are the commonly seen bony lesions in patients with recurrent dislocation shoulder. Computed tomography (CT) scan is considered as the best option in assessing the bony defects in the recurrent dislocation shoulder. The aim of this study was to assess the clinical and radiological co-relation in the patients with recurrent dislocation shoulder. Methods Forty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the present case, which was not successfully diagnosed in the emergency department, a CT scan showed the relationships between different bone structures in detail, revealing the glenohumeral dislocation and reverse Hill-Sachs lesion. 21 Several authors recommend using this imaging technique when radiographs are inconclusive, 10 , 11 , 19 and others have noted the importance of complementing CT with magnetic resonance imaging to enable the recognition of associated lesions in the labrum or joint capsule. 20 …”
Section: Discussionmentioning
confidence: 99%
“…In the present case, which was not successfully diagnosed in the emergency department, a CT scan showed the relationships between different bone structures in detail, revealing the glenohumeral dislocation and reverse Hill-Sachs lesion. 21 Several authors recommend using this imaging technique when radiographs are inconclusive, 10 , 11 , 19 and others have noted the importance of complementing CT with magnetic resonance imaging to enable the recognition of associated lesions in the labrum or joint capsule. 20 …”
Section: Discussionmentioning
confidence: 99%
“…For CT, humeral residual articular arc and percentage of articular arc loss, HSL width and depth, percentage of anterior glenoid defect, bare area, on-track and off-track, Franceschi grading, Calandra classification, Richards grading, Hall grading, Rowe grading, Flatow percentage, linear-based and area-based methods were used. 10,31,39,52 The reported sensitivity when confirmed by CT was between 20% and 65%, and the specificity was between 41.7% and 87%. 25,39 Accuracy, positive predictive value (PPV), and negative predictive value (NPV) were not reported amongst the CT studies.…”
Section: Measurement Techniquesmentioning
confidence: 98%
“…10,31,39,52 The reported sensitivity when confirmed by CT was between 20% and 65%, and the specificity was between 41.7% and 87%. 25,39 Accuracy, positive predictive value (PPV), and negative predictive value (NPV) were not reported amongst the CT studies. Intrarater agreement was only reported in one study, where there was 33% agreement for on-track measurements.…”
Section: Measurement Techniquesmentioning
confidence: 98%
“…• young age at the initial dislocation 3,7 • humeral or glenoid critical bone loss at initial dislocation [8][9][10][11] • return to competitive contact sport activities [12][13][14][15] • ligamentous laxity [16][17][18] Recurrent dislocation after initial nonoperative management is closely related to age younger than 20 years at the time of the first dislocation. 3,19 Roberts et al prospectively observed a group of 133 adolescents who were treated nonoperatively for anterior shoulder dislocation and reported a 76% recurrence rate at two years.…”
Section: Risk Factors For Recurrence After Nonoperative Management Of...mentioning
confidence: 99%
“…This recurrence rate drops to 58% and 27% respectively when dealing with an on-track Hill-Sachs lesion or no lesion at all in young first-time dislocators. 8,9 Dickens et al found that initial traumatic anterior shoulder dislocation could lead to minor glenoid bone loss (6.8% of the glenoid width), but this glenoid bone loss increased up to 22.8% in recurring dislocations. 10 In the setting of glenoid bone loss, recurrence rates of 72% in the under 23-year-olds and 27% in the over 30-year-olds have been reported.…”
Section: Risk Factors For Recurrence After Nonoperative Management Of...mentioning
confidence: 99%